Comparison of phase slippage processes in Josephson junctions and in charge density wave stacked junctions - Latyshev, Yu.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We discuss time–space symmetry in the processes of phase slippage in Josephson junctions and charge densitywave (CDW) stacked junctions. In Josephson junctions phase slip by 2π occurs periodically in time with a period T above critical current with a frequency obeys Josephson relation ν = 1/T = 2eV/h, where V is the voltage on the junction. In CDW stacks at voltage on the stack above threshold value the CDW dislocation appears in the weakest junction of the stack. This phase dislocation corresponds to the local phase slippage by 2π. With voltage increase a new dislocations appear forming periodic array of dislocations with a period L. The inverse spacing 1/L follows the analog of Josephson equation vF/L = 2eV/h.